Plantar fasciitis in 19 endurance horses: Diagnosis, treatment and follow‐up. (6th October 2020) - Paris, A.; Beccati, F.; Pepe, M.
Summary: Lesions of the peritendinous–periligamentous soft tissues of the tarsus (plantar fasciitis) commonly result in a curb‐like appearance and are considered overrepresented in Standardbred racehorses; however, plantar fasciitis is also quite common in endurance horses. Nineteen endurance horses of different ages (median: 7 years; range: 3–13) and athletic activity level comprising a total number of 25 plantar fasciitis cases were described in this study. In nine cases, injury developed during a training session, and in 16 cases, it developed during competition. In 18 cases, there was swelling, heat and pain on palpation, and in six cases, only swelling was detected. Eight cases were not lame at the time of examination, while in 17 cases, lameness ranged from grades 1–3 on the American Association of Equine Practitioners modified grading scale. The degree of swelling was significantly related to the lameness grade. Ultrasonography revealed differing amounts of thickening of the plantar fascia plantar to the superficial digital flexor tendon and peritendinous–periligamentous oedema of heterogeneous appearance. Horses were treated conservatively with several combinations of rest, controlled exercise, ice‐therapy, corticosteroids, local application of working counterirritants and therapeutic shoeing. Seventeen of 25 cases (68%) did not develop re‐injury after treatment and rehabilitation, whilst eight of 25 (32%) developed one or more re‐injury/injuries. Overall, 21 of 25 cases (84%) returned to the previous or a higher level of competition; in one case (4%), the injury was the cause of retirement from athletic activity. Plantar fasciitis can be considered a sport‐related injury in endurance horses of all ages and athletic activity level. Re‐injury rate is low; however, adequate rest and rehabilitation protocols are important. Plantar fasciitis rarely leads to retirement from athletic activity, but it can result in 2–5 months out of training and competition.